1999
DOI: 10.1007/s002590050383
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral blood flow single-photon emission tomography with 99m Tc-HMPAO and the acetazolamide test in the evaluation of vascular and Alzheimer's dementia

Abstract: The diagnostic potential of technetium-99m hexamethylpropylene amine oxime (HMPAO) following systemic administration of the cerebral vasodilator acetazolamide (acetazolamide test) was evaluated by regional cerebral blood flow (rCBF) single-photon emission tomography (SPET) in patients with Alzheimer's disease (AD) or vascular dementia (VD). An initial, high-resolution SPET study was performed with 99mTc-HMPAO, and after 2 days the patients were re-evaluated with 99mTc-HMPAO following systemic administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…For example, Nagata et al 5 measured MTT and VR to carbon dioxide inhalation in patients with AD and VD and found that MTT was prolonged and VR was depressed in patients with VD, whereas the 2 indices were preserved in patients with AD. 5 Impairment in the responsiveness to vascular activation in VD was reported by De Reuck et al, 15 whereas other groups found no such impairment in AD based on SPECT [16][17][18] and xenon-enhanced CT 19 analysis. Moreover, Puls et al 20 revealed, by using transcranial sonography, that tissue transit time is prolonged in VD but not in degenerative dementia.…”
Section: Discussionmentioning
confidence: 87%
“…For example, Nagata et al 5 measured MTT and VR to carbon dioxide inhalation in patients with AD and VD and found that MTT was prolonged and VR was depressed in patients with VD, whereas the 2 indices were preserved in patients with AD. 5 Impairment in the responsiveness to vascular activation in VD was reported by De Reuck et al, 15 whereas other groups found no such impairment in AD based on SPECT [16][17][18] and xenon-enhanced CT 19 analysis. Moreover, Puls et al 20 revealed, by using transcranial sonography, that tissue transit time is prolonged in VD but not in degenerative dementia.…”
Section: Discussionmentioning
confidence: 87%
“…19 -25 Several earlier studies reported reduced cerebral blood flow in AD. [5][6][7][22][23][24][25]28,29 Pavics et al, 30 studying regional cerebral blood flow, showed that bilateral cerebral hypoperfusion occurs in the temporal and/or parietal region in 70% (23/33) of patients with AD and in 33% (6/18) of patients with vascular dementia. Many authors have concluded that diffuse cerebral hypoperfusion is responsible for leukoaraiosis in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical measurements of regional CBF by the noninvasive SPECT method have indicated that AD is accompanied by a decreased regional CBF in the hippocampal formation, the temporal cortex, the parietal cortex and the frontal cortex [4,11,13,29,36,40,41,46,53]. The region specificity is remarkable because the typical neuropathological hallmarks of AD also appear first and most extensively in the entorhinal region and the temporal cortex.…”
Section: Hypertension Dementia and Cbfmentioning
confidence: 94%